2019
DOI: 10.3390/coatings9020089
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Interface Morphology Characterization of Thermal Barrier Coatings Using Terahertz Time-Domain Spectroscopy

Abstract: In this work, a terahertz time-domain spectroscopy (THz-TDS) system was used to measure the thickness of thermal barrier coatings (TBCs) and characterize the interface morphology of TBCs after erosion. Reflection mode, with an angle of incidence of 0, was used for inspection before and after erosion. The refractive index, thickness, and internal structure evolution tendency of the yttria-stabilized zirconia (YSZ) top coat were estimated under consideration of the interaction between the pulsed THz waves and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…In [49], the authors demonstrated the use of THz pulse reflection to measure the topcoat thickness; the results were verified with microscopic imaging to be within measurement error. In [50], a similar measurement was carried out with a custom erosion platform to simulate topcoat erosion in the real operating environment. The measurement was validated with the micrometer (see Figure 5 and Table 1).…”
Section: Thermal Barrier Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [49], the authors demonstrated the use of THz pulse reflection to measure the topcoat thickness; the results were verified with microscopic imaging to be within measurement error. In [50], a similar measurement was carried out with a custom erosion platform to simulate topcoat erosion in the real operating environment. The measurement was validated with the micrometer (see Figure 5 and Table 1).…”
Section: Thermal Barrier Coatingsmentioning
confidence: 99%
“…Photograph of the thermal barrier coating sample after artificial erosion. Spots A, B, and C has undergone increasing degrees of erosion and were scanned using THz reflection spectroscopy [50].…”
Section: Thermal Barrier Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of contact methods is limited by the need for good physical contact with the coated surface and therefore the development of non-contact optical methods has also been necessary. THz time-domain spectroscopy (TDS) [6][7][8][9][10] enables either the thickness or the refractive index of the coating to be determined by measuring the time delay of an ultrashort pulse (∼500 fs -2 ps duration) through the sample. THz illumination is preferred because TBCs are opaque at visible optical frequencies and GHz illumination does not provide adequate resolution for the thin coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Significant technological advances have led to increasing operating temperatures and pressures in recent decades, enhancing the efficiency of gas turbines to over 40%. These technological advances include coatings, heat treatments, a new superalloy permitting high operating temperatures, and a new cooling system [4][5][6][7][8][9][10][11]. Specifically, an F-class gas turbine, which operates at approximately 1300 • C and a pressure ratio of 16 during full-load conditions, was developed in the late 1990s and deployed to many thermal power plants.…”
Section: Introductionmentioning
confidence: 99%